2020
DOI: 10.3390/ijerph17239112
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Practice of Oral Health Measures in Medina, Saudi Arabia: An Observational Study

Abstract: The aim of this observational study is to investigate the oral health status and practices in the multicultural community of Medina, Saudi Arabia. A cross-sectional questionnaire was distributed that asked about oral health, dental and periodontal conditions, personal attitudes toward dental care, and smoking habits. Cross tabulation with chi-squared testing was carried out to investigate the association of toothbrush usage and smoking with several variables. Four-hundred and sixty subjects enrolled in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…In the present study, the report of halitosis was 34.4% among individuals with DS, regardless of age groups. This finding is in agreement with other studies on the prevalence of self-reported halitosis in the normotypic population 11,25,26 and are reinforced by the findings of a systematic review with population-based studies that found a prevalence of 31.8% (24.6−39.0%). 17 This systematic review indicated that the diagnostic method (selfreport, organoleptic evaluation and analysis of volatile sulfur compounds) does not seem to influence the prevalence of halitosis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the report of halitosis was 34.4% among individuals with DS, regardless of age groups. This finding is in agreement with other studies on the prevalence of self-reported halitosis in the normotypic population 11,25,26 and are reinforced by the findings of a systematic review with population-based studies that found a prevalence of 31.8% (24.6−39.0%). 17 This systematic review indicated that the diagnostic method (selfreport, organoleptic evaluation and analysis of volatile sulfur compounds) does not seem to influence the prevalence of halitosis.…”
Section: Discussionsupporting
confidence: 92%
“…The increased occurrence of halitosis with increasing age was previously reported in children 27 . Most halitosis studies were carried out in the adult population 11,17,26 . Studies in children and adolescents showed prevalence rates of 17% to 40%, with self‐reported halitosis being the most frequent (39.67%) 25,27,28 .…”
Section: Discussionmentioning
confidence: 89%
“…With regard to the status of having a family dentist, there are differences among countries. For example, a Canadian study shows 95% of the participants having a family dentist [ 20 ], a Saudi Arabian study shows 22% [ 22 ], and a South African study shows 3% [ 24 ]. However, since healthcare systems vary from country to country, it is impossible to simply compare these proportion values.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the Japan Dental Association is enlightening the Japanese people to have a family dentist with whom they can consult for any oral health issues [ 14 ]. It has been reported that the system and ratio of having a family dentist varies greatly from country to country [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]; however, generally, having a family dentist is associated with maintaining good oral health status [ 16 , 19 , 23 ]. Furthermore, the studies conducted in this country showing the percentage and characteristics of those having a family dentist in certain local regions exist [ 16 , 17 , 18 , 19 ]; however, few studies have analyzed them on a nationwide scale.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the government's efforts, the population's awareness of preventive oral healthcare is limited for various reasons, including the absence of structured prevention and education programs, and a lack of awareness campaigns [12,13]. Financial constraints can contribute to the low awareness levels among the population.…”
Section: Introductionmentioning
confidence: 99%